Determination of whether morphometric analysis of vertebrae in the domestic cat (Felis catus) is related to sex or skull shape - Burin Boonsri (2020)
© 2020, Japanese Association of Anatomists. In many mammals, gender and skull shape are related to the bone morphology of the entire body; however, this has not been well established in the domestic cat (Felis catus). This study aims to find a relationship between cervical, thoracic and lumbar vertebrae morphometrics with regard to the sex and skull shape of domestic cats. A total of 79 samples obtained from 92 dried bones of domestic cats were used to determine morphometric measurements for a total of 29 parameters. Hierarchical clustering was used to cluster the vertebral bones found in three groups: C3-T1, T2-T11 and T12-L7. The skull shape identification process employed discriminative analysis and revealed the highest training data accuracy rate at up to 86.20% in T4 followed by L1 (86.04%) Axis (85.71%) and C5 (85.18%). Sex identification employed discriminative analysis and displayed the highest training data accuracy rate at up to 75.58% in L1 followed by, T7 (71.87%) and C6 (71.79%). Moreover, we found that 14% of the samples had one vertebra missing (T13 or L1). In conclusion, domestic cat vertebral morphometrics were found to be more related to skull shape than gender. In addition, bone clustering employed morphometric data and yielded a result that was similar to that of traditional cluster analysis involving body regions.